Makna Teologis Misa Syukur Panen dalam Konteks Budaya Dayak Kalimantan Barat - Tryepina Paulina Nona; Intansakti Pius X (Fakultas Teologi, Universitas Sanata Dharma, 2026)
This article is based on the harvest thanksgiving tradition in Dayak culture in West Kalimantan, which finds significant intersection with the celebration of the Harvest Thanksgiving Mass in the Catholic Church, presenting a phenomenon of profound faith inculturation. Aiming to explore the theological meaning of the Harvest Thanksgiving Mass, this study positions the celebration as a concrete form of encounter between Christian faith and local Dayak wisdom. Using a qualitative method with a theological and anthropological literature review approach, this study analyzes the relationship between traditional rites and the Church's liturgy. The results of this article show that the Harvest Thanksgiving Mass is not merely an expression of gratitude, but contains rich theological meaning, including the dimensions of universal gratitude, strengthening the fellowship of the people, and renewing reconciliation between humans, nature, and the Creator. Overall, the Harvest Thanksgiving Mass functions as a concrete manifestation of the Catholic Church's inculturative faith, which is dynamic and deeply rooted in the Dayak cultural context.AbstrakArtikel ini berlatar belakang dari tradisi syukur panen dalam kebudayaan Dayak di Kalimantan Barat yang menemukan titik temu signifikan dengan perayaan Misa Syukur Panen dalam Gereja Katolik, menyajikan sebuah fenomena inkulturasi iman yang mendalam. Bertujuan untuk menggali makna teologis Misa Syukur Panen, studi ini menempatkan perayaan tersebut sebagai bentuk konkret perjumpaan iman Kristiani dan kearifan lokal Dayak. Menggunakan metode kualitatif dengan pendekatan tinjauan pustaka teologis dan antropologis, penelitian ini menganalisis relasi antara ritus adat dan liturgi Gereja. Hasil artikel ini menunjukkan bahwa Misa Syukur Panen tidak hanya sekadar ungkapan terima kasih, namun mengandung makna teologis yang kaya, meliputi dimensi syukur universal, penguatan persekutuan umat, serta pembaruan rekonsiliasi antara manusia, alam, dan Sang Pencipta. Secara keseluruhan, Misa Syukur Panen berfungsi sebagai wujud nyata iman inkulturatif Gereja Katolik yang secara dinamis dan hidup berakar kuat dalam konteks budaya Dayak.